Profile of Pencak Silat Competition Techniques: New Rules for the 2023 Cambodia Sea Games - Yulianto, Febri; Subekti, Nur; Kuswanto, Cahniyo Wijaya; Fiqri, Muhammad (Universitas Negeri Padang, 2023)
Background and aim. The aim of this research is to conduct a comparison with previous studies and to identify the dominant technical actions in the 2023 SEA Games Cambodia elite-level pencak silat competition using the new PERSILAT 2022 regulations.Methods This study employs a quantitative approach using observation-survey methods on 9 elite athletes, consisting of 5 male and 4 female athletes. Data were collected by observing match videos from the preliminary rounds to the finals, recording all technical actions (punches, kicks, and throws), and analyzed using SPSS.Results. The findings indicate that side kick techniques reached 24%, front kicks 18%, and throwing techniques 28%. These results differ significantly from previous studies. Under the PERSILAT 2022 regulations, throwing techniques emerged as the most dominant action in pencak silat competitions.Conclusions. The results can serve as a reference for coaches and practitioners in designing training programs by considering rule changes and the effectiveness of athletes’ tactical performance to achieve optimal results.